2015
DOI: 10.1021/acs.jpcc.5b07813
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Oxygen-Vacancy Migration in the Fluorite Oxide CeO2: An Ab Initio Study of Impurity-Anion Migration

Abstract: The site exchange of an anion moiety (O, N, F, Ne, P, S, Cl, and Ar) with an oxygen vacancy in fluorite-structured CeO2 was studied by means of density functional theory (DFT) calculations. The obtained activation energies of migration vary between 0.2 and 0.9 eV, and increase with the formal valence of the migrating ion; the size of the migrating ion appears to play a minor role. An analysis of ion displacements suggests that repulsive Coulombic interactions between the migrating anion and oxygen ions as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 56 publications
2
23
1
Order By: Relevance
“…The reason for this could be that the migration of single charged F − is less hindered than the migration of the double charged -O 2 . Genreith-Schriever et al [28] examined using computational methods the migration behaviour of various anions in CeO 2 and found that a higher negative charge on the migrating ion leads to a higher migration barrier. This would support our explanation for the observed difference between the F − and the -O 2 migration.…”
Section: Literature Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this could be that the migration of single charged F − is less hindered than the migration of the double charged -O 2 . Genreith-Schriever et al [28] examined using computational methods the migration behaviour of various anions in CeO 2 and found that a higher negative charge on the migrating ion leads to a higher migration barrier. This would support our explanation for the observed difference between the F − and the -O 2 migration.…”
Section: Literature Discussionmentioning
confidence: 99%
“…One class of materials, for which both cases have been studied, is the family of AO 2 fluorite-structured oxides, such as ZrO 2 , HfO 2 , CeO 2 , ThO 2 , UO 2 and PuO 2 . Most of the published computational studies on these materials, however, only report activation barriers for oxygen-vacancy migration (from static calculations either based on densityfunctional-theory calculations [23][24][25][26][27][28][29] or based on empirical pair-potentials calculations [30][31][32][33][34][35]). The activation barrier for vacancy migration is predicted to be in the range of 0.4eV to 0.6 eV.…”
Section: Introductionmentioning
confidence: 99%
“…4) is similar, 48 and it is this environment that is expected to govern the energetics of the migration process. Indeed, according to Genreith-Schriever et al, 49 the repulsive Coulomb interactions between the migrating anion and the surrounding nextnearest-neighbour oxygen ions determine the energetics of anion migration in fluorite-based oxides.…”
Section: B Diffusionmentioning
confidence: 99%
“…It is worth noting that, as revealed by the DFT calculations described later in this paper, the Y dopant atoms can also lower the formation energy of oxygen vacancies in doped ceria and therefore raise the saturation concentration of Ce 3+ . The migration energy for an oxygen ion to travel through the Y-Ce edge is close to that through the Ce-Ce edge (Nakayama & Martin, 2009;Genreith-Schriever et al, 2015). The similar ionic radii of Y 3+ and Ce 4+ also warrants that the Y doping only incurs limited structural deformation.…”
Section: Resultsmentioning
confidence: 93%